SCIDOT-35. A NOVEL MODEL FOR THE OPTIMIZATION OF DRUG-DEVICE COMBINATIONS FOR THE TREATMENT OF BRAIN TUMORS. (11th November 2019) - Killick-Cole, Clare; Woolley, Max; Johnson, David; Lewis, Owen; Moore, Patrick; Fletcher, Julia; Skinner, Paul; Bienemann, Alison; Gill, Steven
Abstract: BACKGROUND: Failure of many brain tumor treatments has been attributed to the inability of a compound to cross the blood-brain barrier. Convection-enhanced delivery (CED) offers a method to administer drugs directly to the tumor site, thereby mitigating this limitation. CED has been used in several preclinical and clinical studies, though an approved treatment is yet to come to fruition. A medical device suitable for repeated intraparenchymal delivery is valuable for brain tumor treatment strategies, but a lack of appropriate preclinical models capable of infusing clinically relevant volumes has hindered progress in clinical translation. Currently utilized preclinical models include porcine, which have limited use due to their growth rates and canine and non-human primates, which are restricted by ethical considerations. This study investigates the functional characteristics and stability of the Renishaw clinical Neuroinfuse™ drug delivery system in an ovine model. METHODS: A head fixation frame was refined for ovine stereotactic surgery. Eight Romney ewes were implanted with the drug delivery system, comprising of four catheters and a transcutaneous port allowing chronic re-access infusions without repeated surgery. A maximum of four infusions were performed per subject, at four to eight-week intervals. RESULTS: The implantation of the Neuroinfuse™ drug delivery system was well-tolerated in all subjects, without serious device related adverse events. Artificial CSF/gadolinium infusions were performed on five subjects. Three subjects were maintained for a follow-up study. Putaminal and thalamic distribution volumes remained stable over the re-access period of up to six months post-implantation. CONCLUSION: Romney ewes are suitable for the stereotactic implantation of the Neuroinfuse™ chronic drug delivery system. Transcutaneous ports remained integrated for the study duration, allowing repeated intraparenchymal delivery. This novel preclinical model provides a stable platform for infusion regime optimization of drug-device combinations for chronic CED, which will undoubtably de-risk clinical translation in the neuro-oncology CED field.